Efficacy of allergen-specific immunotherapy in children with atopic dermatitis sensitized to house dust mites - O.V. Mozyrska (Zaslavsky O.Yu., 2022)
Background. Allergen-specific immunotherapy is the mainstay of treatment for inducing long-term immune and clinical tolerability of allergens in patients with IgE-mediated allergic diseases. The aim of this study was to investigate the role of sublingual immunotherapy (SLIT) as an adjunct treatment in children with atopic dermatitis sensitized to dust mites by conducting a randomized 18-month clinical trial with house dust mite extract or placebo. Materials and methods. The study included 26 children with atopic dermatitis who were sensitized to house dust mites. 12 patients received SLIT, and 14 controls received only symptomatic treatment. The activity of atopic dermatitis was assessed using the dynamics of SCORAD indicators and the СDLQI questionnaire. Results. After 18 months of treatment, the reduction in baseline SCORAD was 43.4 % in the SLIT group and 10.3 % in the placebo group (W = 104.0, p = 0.003). СDLQI also showed improvement in the SLIT treatment group (40.7 % in the SLIT group, no improvement was found in the control group, W = 106.5, p = 0.004). There were no significant differences in serum Der.p.-specific sIgE levels between the main and control groups 18 months after the start of treatment (p > 0.05). Conclusions. SLIT with dust mite extract can provide significant clinical efficacy among children with atopic dermatitis, as evidenced by a significant overall reduction in SCORAD scores and СDLQI questionnaire scores.